CHILD SEXUAL ABUSE: PUBLIC POLICY PROPOSALS - Róbinson Orlando Freitas Palominio (Artefactum - revista de estudos interdisciplinares, 2026)
Children and adolescents are the primary victims of violence; in this regard, this article seeks to discuss the impact that sexual violence has on the lives of children and adolescents. To this end, the article will present the legal framework regarding the rights of children and adolescents, the definition of sexual violence and its types, as well as the possible consequences that will shape the life of the victim. This is a bibliographic study that utilized the following search terms: sexual violence, child abuse, and consequences of child sexual abuse. The literature review yielded several key findings, including the observation that child sexual abuse is predominantly domestic in nature. Furthermore, studies point to a significant increase in the predisposition to alcoholism, drug abuse, depression, and suicidal ideation in adulthood, reinforcing the negative, lifelong impact of childhood and adolescent violence.